Advances in Disease-Modifying Therapeutics for Chronic Neuromuscular Disorders - Davalos, Long; Kushlaf, Hani (Seminars in Respiratory and Critical Care Medicine, 2024)
Neuromuscular disorders can cause respiratory impairment by affecting the muscle fibers, neuromuscular junction, or innervation of respiratory muscles, leading to significant morbidity and mortality. Over the past few years, new disease-modifying therapies have been developed and made available for treating different neuromuscular disorders. Some of these therapies have remarkable effectiveness, resulting in the prevention and reduction of respiratory complications. For myasthenia gravis (MG), efgartigimod, ravulizumab, rozanolixizumab, and zilucoplan have been Food and Drug Administration (FDA)-approved for the treatment of acetylcholine receptor (AChR) antibody-positive generalized MG in the past 2 years. Rozanolixiumab is also approved for treating MG caused by muscle-specific tyrosine kinase (MuSK) antibodies. The new MG therapeutics target the complement system or block the neonatal fragment crystallizable (Fc) receptors (FcRn), leading to significant clinical improvement. For spinal muscular atrophy (SMA), nusinersen (intrathecal route) and risdiplam (oral route) modify the splicing of the SMN2 gene, increasing the production of normal survival motor neuron (SMN) protein. Onasemnogene abeparvovec is a gene replacement therapy that encodes a functional SMN protein. All SMA medications, particularly onasemnogene abeparvovec, have led to clinically meaningful improvement. For late-onset Pompe disease (LOPD), avalglucosidase alfa has shown a greater improvement in respiratory function, ambulation, and functional outcomes in comparison to alglucosidase alfa, and cipaglucosidase alfa combined with miglustat has shown improvement in respiratory and motor function in a cohort of enzyme replacement therapy-experienced LOPD patients. Amyotrophic lateral sclerosis (ALS) remains a challenge. The two most recent FDA-approved medications, namely sodium phenylbutyrate and tofersen, may slow down the disease by a few months in a selected population but do not stop the progression of the disease.
Keywords: amyotrophic lateral sclerosis; myasthenia gravis; spinal muscular atrophy; late-onset Pompe disease; neuromuscular disorders; therapy